Associations between circulating components of the renin-angiotensin-aldosterone system and left ventricular mass. - Schunkert, H. (1997)
OBJECTIVE: Cardiac growth may be modulated in part by the trophic effects of neurohormones. The aim of the present study was to investigate the relation between the basal activity of the renin-angiotensin-aldosterone system and left ventricular mass. DESIGN: A population based sample of 615 middle-age subjects was studied by standardised echocardiography; anthropometric measurements; and biochemical quantification of renin, pro-renin, angiotensinogen, angiotensin converting enzyme (ACE), and aldosterone. RESULTS: Echocardiographic left ventricular mass index correlated significantly with arterial blood pressure, age, and body mass index. In addition, in men ACE activity was significantly related to left ventricular mass index in univariate (P = 0.0007) and multivariate analyses (P = 0.008). Men with left ventricular hypertrophy presented with significantly higher serum ACE concentrations than those with normal left ventricular mass index (P = 0.002). In both men and women serum aldosterone was strongly related to septal and posterior wall thickness. Furthermore, in women serum aldosterone was positively and independently associated with left ventricular mass index (P = 0.0001). This effect was most prominent in hypertensive women. Finally, women with left ventricular hypertrophy presented with significantly higher serum aldosterone (P = 0.01). No significant associations with left ventricular mass index were observed for angiotensinogen, renin, or pro-renin. CONCLUSIONS: The data suggest that the variability of serum ACE or aldosterone, as occurred in this large population based sample, may contribute to the modulation of left ventricular mass.